MANAGEMENT OF A RARE CASE OF PEG MANDIBULAR CENTRAL INCISOR - Shijee M; Ponnudurai Arangannal; Jeevarathan; Janani Vinodhini; Madhumitha; Ramya Chellamal; Ishwarya Dhevi G R (The Bioscan, 2024)
Developmental disturbances of teeth may result from disturbances in any developmental stage of teeth which may be unknown,genetic or environmental factors.Depending upon time and location of disturbance,changes are evident in the normal number,size,shape and structure of tooth.Non-syndromic microdontia is rarely noted,especially in permanent mandibular incisors.This is one such case report of a 9 year old female patient in whom management was done with prime concern of restoring the esthetics conservatively by using strip crown.